Lüge, Hochstapelei und Bildung: Bildungstheoretische Annäherungen und biographische Rekonstruktionen - Schmidt, Katja (transcript, 2018)
Can you talk about educational processes when these spill over into the dimension of lying? And: What does imposture have to do with (adult) education?